Feeling political : emotions and institutions since 1789 /: emotions and institutions since 1789. (2021) - Frevert, Ute; Pahl, Kerstin Maria; Buscemi, Francesco; Nielsen, Philipp; Arndt, Agnes; Amico, Michael; Lichau, Karsten; Malone, Hannah; Wambach, Julia; Brauer, Juliane; Moine, Caroline
No abstract available